2014
DOI: 10.1002/chem.201404091
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Study of Dihydrogen Phosphate Dimerisation and Complexation with Novel Urea‐ and Thiourea‐Based Receptors

Abstract: Complexation of dihydrogen phosphate by novel thiourea and urea receptors in acetonitrile and dimethyl sulfoxide was studied in detail by an integrated approach by using several methods (isothermal titration calorimetry, ESI-MS, and (1)H NMR and UV spectroscopy). Thermodynamic investigations into H2PO4(-) dimerisation, which is a process that has been frequently recognised, but rarely quantitatively described, were carried out as well. The corresponding equilibrium was taken into account in the anion-binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…1a ). Phosphate oligomerization has been seen in solution 38 , 39 even without receptors and was previously modelled 14 in acetonitrile as a simple monomer–dimer equilibrium ( K dimer = 2400 M –1 ) where 66% of the phosphate is dimerized at 1 mM. Presumably, the propensity of phosphate to oligomerize as well as the characteristics of the receptors will help determine the types of complexes it forms.…”
Section: Introductionmentioning
confidence: 99%
“…1a ). Phosphate oligomerization has been seen in solution 38 , 39 even without receptors and was previously modelled 14 in acetonitrile as a simple monomer–dimer equilibrium ( K dimer = 2400 M –1 ) where 66% of the phosphate is dimerized at 1 mM. Presumably, the propensity of phosphate to oligomerize as well as the characteristics of the receptors will help determine the types of complexes it forms.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, Perez‐Casas and Yatsimirsky have shown that in some cases the same data could be fitted to both “apparent association constant” and to the overall constant involving multiple equilibria including proton transfer with sufficient quality . These, and other authors pointed out the importance of self‐association of anions with their conjugate acids in non‐aqueous media and this equilibrium is also included in K app . The K app will serve for the comparison with literature data and those obtained by titration of selected benzoylthioureas ( BTU1 and BTU4 – 6 ) and neutral benzoylguanidines ( 4 and 6 ) prepared in this work.…”
Section: Resultsmentioning
confidence: 99%
“…As a control, no peaks were observed in the same region in studies conducted with perchlorate (Figure c) or when bisulfate (Figure d) was examined in the absence of cyanostar at near saturated concentrations (1 M). Furthermore, careful scrutiny of all prior works claiming the observation of H 2 PO 4 − dimers, did not find any corresponding signature of a hydrogen bonded −OH group.…”
Section: Figurementioning
confidence: 88%
“…Nevertheless, there are no direct observations of anion dimers in solution. With good reason, the authors of those works, Reinhoudt, Kubo, Fabbrizzi, Sessler, and Tomisič, took care to circumscribe these claims with caveats such as “tentatively assigned”. The idea that anions can be bound to each other in solution in a complex has yet to be substantiated.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation